Responsibilty Of the Wife as Breadwinner in Indonesia Law (Case Study of The Wife in Imbanagara Village Ciamis Regency) - Raihan, Muhammad Aulia; Sanjaya, Umar Haris; Amiludin, Amiludin; Albab, Ulil (Universitas Muhammadiyah Tangerang, 2023)
Law Number 1 of 1974 about marriage explains in Article 31 paragraph (1) that the rights and position of the wife are balanced with the rights and position of the husband in domestic life and the association of living together in society. Furthermore, article 34, paragraph (1) states that the husband is obliged to protect his wife and provide everything necessary for married life in accordance with his capability. In practice, it is found that the wife should be responsible for making a living for her family, this is not in accordance with the ideal marriage law that should be between husband and wife equally responsible for earning a living for their family. The problem in this study is the wife's responsibility as a breadwinner and the regulations of the wife as the breadwinner in Indonesian law. This type of research, in this case, is empirical juridical legal research. Empirical juridical research in other words, is a type of sociological research and can be called research in the field, which examines legal provisions and what occurs in people's lives. The location of this research is Imbanagara Village, Ciamis Regency. The source of this research data is in the form of primary legal material, secondary and tertiary, namely, laws and regulations, journals, and dictionaries as support. The rights and position of husband and wife are balanced; husband and wife are obliged to be responsible in their household, and the wife can be the breadwinner because of her equal rights and position in Islamic law the wife is not obliged to work, the husband is obliged to earn a living.Keywords: Responsibility, Breadwinner, Wife, Husband